2007
DOI: 10.1021/jo701443c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Urea Picket Porphyrins and Their Use in the Elucidation of the Role Buried Solvent Plays in the Selectivity and Stoichiometry of Anion Binding Receptors

Abstract: The synthesis of alpha,alpha-5,10-diurea and alpha,alpha,alpha-5,10,15-triurea picket porphyrins are detailed in this report. In previous reports, these porphyrins, along with alpha,alpha,alpha,alpha-5,10,15,20-tetraurea picket porphyrin, were used to demonstrate the important role one buried solvent molecule plays in the selectivity and stoichiometry of binding inorganic anions. Building on prior work, this report discusses the results of acetate anion binding studies between tetra- and diurea picket porphyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 33 publications
(60 reference statements)
1
34
1
Order By: Relevance
“…57 Pt II , as a d 8 cation, has a defined preference for square coordination and . 56 Structures redrawn from data deposited at the Cambridge Crystallographic Data Centre (VAVCUQ, TISSIY, TISSOE). SO 4 2À (added as a Na + salt) indicated the formation of 1 : 1 complexes, with K > 10 5 for both anions.…”
Section: Taking Profit From Metals To Enhance Receptor's Binding Propmentioning
confidence: 99%
See 1 more Smart Citation
“…57 Pt II , as a d 8 cation, has a defined preference for square coordination and . 56 Structures redrawn from data deposited at the Cambridge Crystallographic Data Centre (VAVCUQ, TISSIY, TISSOE). SO 4 2À (added as a Na + salt) indicated the formation of 1 : 1 complexes, with K > 10 5 for both anions.…”
Section: Taking Profit From Metals To Enhance Receptor's Binding Propmentioning
confidence: 99%
“…Tetrabutylammonium counter-cations and the hydrogen atoms of C-H fragments of each receptor have been omitted for clarity; (a) receptor 34, whose cavity includes a Cl À ion and a DMSO molecule; 54 (b) receptor 33, including two Cl À ions;56 (c) receptor 33 including the H-bond dimer [H 2 PO 4 ] 2 2À…”
mentioning
confidence: 99%
“…These solid state differences are consistent with the disparities in binding stoichiometry seen from Job plot analysis when anion-binding studies are carried out in different solvents. 63 As noted above, sapphyrins were first appreciated for their anion-binding ability in the early 1990s. Several X-ray crystal structures have been elucidated and revealed the ability of the protonated macrocycle to bind anions; Figure 32 shows a sapphyrin derivative, 32, in its diprotonated form, which is bound to two bromides.…”
Section: Anionsmentioning
confidence: 97%
“…This results in an anion-bound complex of greater stability than that produced by the corresponding porphyrin functionalized with just two urea pickets in the 5 and 10 positions (ortho). 63 On the basis of detailed studies of the thermodynamics of complexation, it was inferred that one buried solvent molecule adds the equivalent of an "additional" hydrogen bond in terms of anion affinity. These researchers also concluded that a buried solvent molecule can affect the receptor: anion-binding stoichiometry.…”
Section: Anionsmentioning
confidence: 99%
“…29,35 Later, it was shown that stoichiometry 1:2 can be due to the formation of two 36 or 3 intermolecular H-bonds between two H2PO4 -anions. 37 This cooperative effect additionally stabilizes 1:2 stoichiometries rendering them more stable than the …”
Section: Anion Binding In the Solutionmentioning
confidence: 99%